Agreement on revision of "Research Agreement" between Nippon Telegraph and Telephone Corporation, Japan and Universiti Teknologi Malaysia - Universiti Teknologi Malaysia; Nippon Telegraph and Telephone Corporation (NTT) (Skudai : Universiti Teknologi Malaysia, 1998)
18